Success factors for Taiwanese contractors collaborating with local Chinese contractors in construction projects - Kao, Chih-Han; Huang, Cheng-Han; Hsu, Mark Shu-Chien; Tsai, I-Hung (Journal of Business Economics and Management, 2016)
Regional trade cooperation has become an important component of construction industry due to the Free Trade Agreement. This segment of the market presents many challenges for construction firms. Establishing suitable international partnering relations is an effective strategy for adapting to the additional unpredictability of international markets. This research integrates the Balanced Scorecard system with Fuzzy Analytic Hierarchy Process for comprehensive and quantitative evaluation of the relevant bilateral cooperation. Commercial cooperation across the Taiwan Strait is selected as a case study for determining the evaluating methodology. After examining data from Chinese firms, 12 factors for partner selection are identified. The factors are compared with practical conditions of worldwide and local markets to establish their viability. The methodology provides a framework for evaluating potential partners when attempting to enter foreign markets. Additionally, it identifies critical factors for developing optimal market entrance strategies, contracts, and risk management; results can also be golcally (globally and locally) tailored to promote the efficiency of international cooperation.